2017
DOI: 10.1002/casp.2305
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice in interreligious context: The role of metaprejudice and majority–minority status

Abstract: Samples of two hundred forty‐five majority Sunny Muslims, 87 Ahmadiyya Muslims, and 145 Christians were used to investigate the determinants and mediators of prejudice in interreligious context in Indonesia. First, the study extends the idea of in‐group and out‐group metaprejudice; both of which were found to mediate the relationship between perceived quality of intergroup relationship and personal prejudice. Second, we expected that majority members are more likely to reject a minority and that a minority is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 39 publications
5
32
0
2
Order By: Relevance
“…Importantly, the effects of felt understanding were distinct from the concurrent main effects of felt liking, increasing our confidence that it is the extent to which felt understanding involves 'our' perspectives in the eyes of outgroup members that explains its positive effects, as distinct from the likewise positive effects of simply being seen positively by an outgroup per se. An alternative design that did not orthogonally manipulate felt understanding and felt liking would therefore have provided less clarity about whether any effect of felt understanding was due to the meta-meta perspective (our perspective on their perspectives on our perspectives) that it involves, or was more straightforwardly explicable in terms of the lower-order (meta-) perception of felt liking (e.g., Owuamalam et al, 2014;Putra & Wagner, 2017). More broadly, the present findings are consistent with the only other work on the predictive effects of felt understanding, which showed that it predicted outcomes such as trust, political separatism, and post-conflict forgiveness over and above predictors such as stereotypes, meta-stereotypes, and different forms of threat perception in cross-sectional surveys (Livingstone et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Importantly, the effects of felt understanding were distinct from the concurrent main effects of felt liking, increasing our confidence that it is the extent to which felt understanding involves 'our' perspectives in the eyes of outgroup members that explains its positive effects, as distinct from the likewise positive effects of simply being seen positively by an outgroup per se. An alternative design that did not orthogonally manipulate felt understanding and felt liking would therefore have provided less clarity about whether any effect of felt understanding was due to the meta-meta perspective (our perspective on their perspectives on our perspectives) that it involves, or was more straightforwardly explicable in terms of the lower-order (meta-) perception of felt liking (e.g., Owuamalam et al, 2014;Putra & Wagner, 2017). More broadly, the present findings are consistent with the only other work on the predictive effects of felt understanding, which showed that it predicted outcomes such as trust, political separatism, and post-conflict forgiveness over and above predictors such as stereotypes, meta-stereotypes, and different forms of threat perception in cross-sectional surveys (Livingstone et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The common theme in this previous research is that group members are concerned with the perceptions and image that members of outgroups have of an ingroup. These include meta-stereotypes (Vorauer et al, 1998), meta-prejudice (Owuamalam et al, 2014;Putra, 2014;Putra & Wagner, 2017), and meta-dehumanization (Kteily et al, 2016). These each address ingroup perspectives on outgroup perspectives (of us), and have been shown to shape intergroup attitudes and behavior.…”
Section: Felt Understanding As a Driver Of Positive Social Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…As we have described in the introduction and in the section on the history of communism in Indonesia, the PKI stigma can impact the lives of people of various ages and in different settings in a very negative way. In our empirical studies we will focus on those expressions of prejudice that could occur nowadays in Indonesia (Putra, 2014;Putra & Wagner, 2017), such as a withdrawal of support for a political candidate or the devaluation of a student's scholarly achievements. In both cases, we assume that merely alleging PKI descent is enough to solicit prejudice towards a person.…”
mentioning
confidence: 99%